Obstetric anaesthetic and analgesic services in Wales. Issue 6192 (22nd September 1979) - Hibbard, B M; Rees, G; Rosen, M
Abstract : A survey of obstetric anaesthetic services in Wales covering 21 major units in which over 31 000 deliveries take place annually showed inadequacies in staffing at consultant and resident anaesthetist level. At least 20 additional consultant sessions were required to meet the recommendations of the Association of Anaesthetists of Great Britain and Ireland. If patients' requests for epidural analgesia are to be met some reorganisation and centralisation of facilities is needed.